APPLYING FUZZY ANALYTIC HIERARCHY PROCESS (FAHP) a-CUT BASED AND TOPSIS METHODS TO DETERMINE REGENCIAL ROAD HANDLING PRIORITY (Case Study: Badung Regency - Bali) - Priyantha Wedagama, D. M.; Rai Andnyana, I. B. (Jurnal Ilmiah Teknik Sipil, 2012)
This study examines regencial road handling priority using FAHP a-cut based and TOPSIS methods using Badung regency in Bali province as the case study area. The study is restricted to regencial roads under severe conditions. Adoption of these FAHP a-cut based and TOPSIS methods allow the researcher to have estimation regarding the overall road handling priority considering the decision makers’s attitude from optimistic to pessimistic situations and decision makers’s degree of confidence from under the most uncertain to certain comparisons. Meanwhile, the previous study has analysed the same case study area using FAHP extent analysis and TOPSIS methods with no consideration on decision makers’s attitude and confidence. This study concluded that road handling determination using FAHP a cut based and TOPSIS methods, considering both pessimistic and moderate situations and highly optimistics situation with uncertain conditions of the decision makers, produced similar top prioty as it used FAHP extent analysis and TOPSIS methods.
Keywords: Road Handling, Fuzzy AHP a-cut based method, TOPSIS